Identification of a new adtrp1‐tfpi regulatory axis for the specification of primitive myelopoiesis and definitive hematopoiesis. Issue 1 (6th September 2017) - Wang, Li; Wang, Xiaojing; Wang, Longfei; Yousaf, Muhammad; Li, Jia; Zuo, Mengxia; Yang, Zhongcheng; Gou, Dongzhi; Bao, Binghao; Li, Lei; Xiang, Ning; Jia, Haibo; et al.
Abstract : A genomic variant in the human ADTRP [androgen‐dependent tissue factor (TF) pathway inhibitor (TFPI) regulating protein] gene increases the risk of coronary artery disease, the leading cause of death worldwide. TFPI is the TF pathway inhibitor that is involved in coagulation. Here, we report that adtrp and tfpi form a regulatory axis that specifies primitive myelopoiesis and definitive hematopoiesis, but not primitive erythropoiesis or vas‐ culogenesis. In zebrafish, there are 2 paralogues for adtrp (i.e., adtrpl and adtrp2 ). Knockdown of adtrpl expression inhibits the specification of hemangioblasts, as shown by decreased expression of the hemangioblast markers, etsrp, flila, and scl ; blocks primitive hematopoiesis, as shown by decreased expression of pu.1, mpo, and l‐plastin ; and disrupts the specification of hematopoietic stem cells (definitive hematopoiesis), as shown by decreased expression of runx1 and c‐myb . However, adtrp1 knockdown does not affect erythropoiesis during primitive hematopoiesis (no effect on gata1 or h‐bae1 ) or vasculogenesis (no effect on kdrl, ephb2a, notch3, dab2, or flt4 ). Knockdown of adtrp2 expression does not have apparent effects on all markers tested. Knockdown of adtrp1 reduced the expression of tfpi, and hematopoietic defects in adtrp1 morphants were rescued by tfpi overexpression. These data suggest that the regulation of tfpi expression is one potential mechanism by which adtrp1 regulates primitive myelopoiesis and definitive hematopoiesis.—Wang L., Wang X., Wang L., Yousaf, M., Li, J., Zuo, M., Yang Z., Gou, D., Bao, B., Li, L., Xiang, N., Jia, H., Xu, C., Chen, Q., Wang Q. K. Identificationofanew adtrp1‐tfpi regulatory axis for the specification of primitive myelopoiesis and definitive hematopoiesis. FASEB J. 32, 183‐194 (2018). www.fasebj.org